Dual-phase synergistic deformation characteristics and strengthening mechanism of AlCoCrFeNi2.1 eutectic high entropy alloy fabricated by laser powder bed fusion. (1st July 2023) - Tang, Xu; Zhang, Hao; Zhu, Zhengwang; Xue, Peng; Wu, Lihui; Liu, Fengchao; Ni, Dingrui; Xiao, Bolv; Ma, Zongyi
Highlights: The optimum process parameters for preparing AlCoCrFeNi2.1 were determined. Formation mechanism of regular eutectic lamella of AlCoCrFeNi2.1 was revealed. The printed AlCoCrFeNi2.1 possessed excellent match of strength and plasticity. The strain hardening effect caused by synergistic deformation was emphasized. Abstract: Eutectic high entropy alloy (EHEA) possesses promising prospects for industrial application due to its controllable and near-equilibrium dual-phase structure. Due to the advantages of high material utilization, efficient production, and design freedom, the laser powder bed fusion (LPBF) technique provides a new path to prepare EHEA components with complex structure and excellent performance. In this study, near fully dense AlCoCrFeNi2.1 samples were obtained by adjusting the process parameters of LPBF. Considering the balling phenomenon and powder splashing during the LPBF process, laser remelting was selected as an optimized scanning strategy to further improve the forming quality of AlCoCrFeNi2.1 . The microstructure of remelted AlCoCrFeNi2.1 sample exhibited regular eutectic lamellae consisting of nano-scale face-centered-cubic (FCC) and B2 phases, in which the FCC phase accounted for a higher proportion. By investigating the tensile behavior and deformation mechanism, it was revealed that the ultrafine eutectic lamellae could induce a strong dual-phase synergistic strengthening, thereby significantly improving the strength of the sample. Compared with the vacuum induction melted (VIM) sample, the remelted sample showed a 54% increase in ultimate tensile strength (UTS -1518 MPa) and a 130% increase in yield strength (YS -1235 MPa) with reasonable plasticity. This study indicates that by combining the design and manufacturing freedom of LPBF with the EHEA, it is expected to fabricate high-property 3D EHEA parts, expanding the application field of EHEA.